Distinguishing synaptic vesicle precursor navigation of microtubule ends with a single rate constant model - M. W. Gramlich (Nature Portfolio, 2021)
Abstract Axonal motor driven cargo utilizes the microtubule cytoskeleton in order to direct cargo, such as synaptic vesicle precursors (SVP), to where they are needed. This transport requires vesicles to travel up to microns in distance. It has recently been observed that finite microtubule lengths can act as roadblocks inhibiting SVP and increasing the time required for transport. SVPs reach the end of a microtubule and pause until they can navigate to a neighboring microtubule in order to continue transport. The mechanism(s) by which axonal SVPs navigate the end of a microtubule in order to continue mobility is unknown. In this manuscript we model experimentally observed vesicle pausing at microtubule ends in C. elegans. We show that a single rate-constant model reproduces the time SVPs pause at MT-ends. This model is based on the time an SVP must detach from its current microtubule and re-attach to a neighboring microtubule. We show that vesicle pause times are different for anterograde and retrograde motion, suggesting that vesicles utilize different proteins at plus and minus end sites. Last, we show that vesicles do not likely utilize a tug-of-war like mechanism and reverse direction in order to navigate microtubule ends.